EFFECT OF OIL PALM MUSHROOM (Volvariella volvaceae) SUBSTITUTION ON PROTEIN CONTENT, TEXTURE, AND ORGANOLEPTIC PROPERTIES OF CHICKEN NUGGETS - Peni Saputra; Hesti Nur’aini; Lina Widawati; Yudian Syahputra; Diah Azhari (Jurnal Saintifik (Multi Science Journal), 2026)
This study aims to analyze the effect of oil palm mushroom (Volvariella volvaceae) substitution on protein content, texture, and organoleptic properties of chicken nuggets. The study used a Completely Randomized Design (CRD) with one factor, namely the ratio of chicken meat to oil palm mushroom consisting of 5 treatments (K1: 400g:0g; K2: 320g:80g; K3: 280g:120g; K4: 240g:160g; K5: 200g:200g). The results showed that oil palm mushroom substitution significantly affected (p<0.05) protein content, texture, and organoleptic properties of chicken nuggets. Protein content ranged from 15.19% to 18.14%, texture values ranged from 172.12 g/mm² to 380.17 g/mm². All treatments met the SNI 01-6683-2002 standard for minimum protein content of chicken nuggets (12%). Higher substitution of oil palm mushroom decreased protein content, texture hardness, and panelist preference for color, taste, and texture of chicken nuggets